Evaluation of the Potential of Biogas Production from Household Food Waste - Wichitsathian, Boonchai; Wonglertarak, Watcharapol; Yimrattanabavorn, Jareeya; Boonyungyuen, Wimonmas (Journal of Advanced Development in Engineering and Science, 2024)
Biogas power generation technology is one of the most viable and environmentally friendly renewable energy sources. This renewable biofuel plays a key role in reducing concerns associated with today’s rapidly increasing energy demand and food waste. This research aims to study the optimum conditions for biogas production from household food waste. The Biochemical Methane Potential (BMP) test was used to determine the potential for methane production. It is a study of the effect of F/M ratio equal to 0.125, 0.167, 0.208, 0.250 d-1. From the study results, it was found that the F/M ratio equal to 0.25 d-1 had the highest total solids removal efficiency and COD at 74.71% and 84.38% with biogas generation rate and methane generation rate equal to 15.433 and 6.64 liters per day. To consider the amount of biogas per organic degradation rate, it was found that it was 73.25 L/Kg TSremove